PENGARUH GAYA BELAJAR, KEMANDIRIAN BELAJAR,DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS XI IPA MAN 1 BANJARMASIN TAHUN PELAJARAN 2022/2023 - Hasby Assidiqi; Muhammad Amin Paris; Raihatul Gina (CV. ADIBA AISHA AMIRA, 2025)
This study aims to (1) describe data on learning styles, learning independence, emotional intelligence, and mathematics learning achievement (2) determine the direct, indirect, and total effects of learning styles, learning independence, and emotional intelligence on the mathematics learning achievement of grade XI IPA students at MAN 1 Banjarmasin in the 2022/2023 academic year. This research is a field research with a quantitative approach. The population in this study were grade XI IPA students at MAN 1 Banjarmasin in the 2022/2023 academic year. The sample in this study consisted of all 101 students of class XI IPA MAN 1 Banjarmasin in the 2022/2023 academic year, and the sample was taken using saturated sampling technique. Data collection techniques included Likert scale questionnaires, documentation, and interviews. The data analysis techniques used in this study were descriptive statistics and classical assumption prerequisite tests, namely normality test, linearity test, multicollinearity test, heteroscedasticity test, and autocorrelation test, as well as path analysis assisted by Lisrel 8.80 software. The results of this study indicate that (1) learning style, learning independence, and emotional intelligence in the good category are positively correlated with students' mathematics learning achievement in the moderate category. (2) There is a significant direct, indirect, and total influence between learning style, learning independence, and emotional intelligence on students' mathematics learning achievement in Grade XI IPA MAN 1 Banjarmasin Academic Year 2022/2023.